Translation, Cultural Adaptation, and Reliability and Validity Testing of a Chinese Version of the Freezing of Gait Questionnaire (FOGQ-CH) - Tao, Ping; Shao, Xuerong; Zhuang, Jie; Wang, Zhen; Dong, Yuchen; Shen, Xia; Guo, Yunjie; Shu, Xiaoyi; Wang, Hong; Xu, Yuanhong; Li, Zhenlan; Adams, Roger; et al. (Frontiers in Neurology, 2021)
Freezing of gait (FOG) is a disabling symptom with a complex episodic nature that is frequently experienced by people with Parkinson’s disease (PD). Although China has the world’s largest PD population, no Chinese version of the freezing of gait questionnaire (FOGQ), the instrument that has been most widely used to assess FOG, has yet been developed. This study aimed to translate and adapt the original version of FOGQ to create a Chinese version, the FOGQ-CH, then assess its reliability, investigate validity. The forward-backwards translation model was adopted, and cultural adaptation included expert review and pretesting. For the reliability study, 31 Chinese native speaking PD patients were assessed twice in 7-10 days interval. Internal consistency and test-retest reliability of the FOGQ-CH were measured by Cronbach’s alpha (Cα) and the Intraclass Correlation Coefficient (ICC). For the validity study, 34 native speakers of Chinese with PD were included. To explore the criterion validity, relationships between the FOGQ-CH and the Unified Parkinson’s Disease Rating Scale Part Ⅱ (UPDRS Ⅱ) and Part Ⅲ (UPDRS Ⅲ), Timed Up and Go Test (TUGT), Timed Up and Go Test in cognitive task (TUGT-Cog), walking speed (10MWT-speed) and step length (10MWT-step length) in 10-Meter Walk Test were tested. To explore predictive validity, the numbers of falls followed up for six months were assessed. The area under the ROC curve (AUC) was employed to test the capacity of FOGQ-CH to discriminate those with falls. The FOGQ-CH was created by translation and cultural adaptation. From the reliability study, Cα =0.823, ICC=0.786. From the validity study, the FOGQ-CH showed moderate correlations with UPDRS Ⅱ (rho=0.560, p=0.001), UPDRS Ⅲ (rho=0.451, p=0.007), TUGT (rho=0.556, p =0.007), TUGT-Cog (rho=0.557, p=0.001), 10MWT-speed (rho=-0.478, p=0.004), 10MWT-step length (rho=-0.419, p=0.014), and the number of falls followed up for 6 months (rho=0.356, p=0.045). The AUC=0.777 (p=0.036) for predicting whether the participants will have multiple falls (two or more) in the following 6 months. The FOGQ-CH showed good reliability and validity for assessing Chinese native speaking PD patients. In addition, the FOGQ-CH showed good efficacy for predicting multiple falls in the following six months.